1997
DOI: 10.1021/jo970665s
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Solvent on the α-Effect:  Nucleophilic Substitution Reactions of p-Nitrophenyl Acetate with m-Chlorophenoxide and Benzohydroxamates in MeCN−H2O Mixtures of Varying Compositions

Abstract: Second-order rate constants have been measured spectrophotometrically for the reactions of p-nitrophenyl acetate (PNPA) with three α-effect nucleophiles, benzohydroxamate (BHA-), p-methylbenzohydroxamate (MBHA-), and p-methyl-N-methylbenzohydroxamate (M2BHA-), and a corresponding normal nucleophile, m-chlorophenoxide (ClPhO-), in MeCN−H2O mixtures of varying compositions at 25.0 °C. The reactivity of ClPhO- and M2BHA- toward PNPA decreases upon additions of MeCN into the reaction medium up to near 30−40 mol % … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Other factors, such as solvent effects, could modify the expression of the α-effect observed, depending on the loci where charge was found. An example of such a possible operation occurs with p -MeNMBH anion reacting with p -nitrophenylacetate in water−acetonitrile mixtures . The only α-nucleophile to show a substantial change in the size of the α-effect was p -MeNMBH anion as the mole percent of MeCN increased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other factors, such as solvent effects, could modify the expression of the α-effect observed, depending on the loci where charge was found. An example of such a possible operation occurs with p -MeNMBH anion reacting with p -nitrophenylacetate in water−acetonitrile mixtures . The only α-nucleophile to show a substantial change in the size of the α-effect was p -MeNMBH anion as the mole percent of MeCN increased.…”
Section: Discussionmentioning
confidence: 99%
“…This idea of internal base catalysis is reported to be responsible for the benzohydroxamate α-effect. Although this idea is known from the early days of the α-effect 12 with this hydroxamic acid chemistry, and although [5] is considered by ref , it seems not to play a great part of the explanation for the large variation of the α-effect with solvent composition for these workers. In fact, their conclusion was that ground-state solvation was not solely responsible for the α-effect they observed, which is at least consistent with our hypothesis that an intrinsic α-effect exists with C atom transfer, and that effect is modified by changes in the type of C atom in the simple CH 3 group.…”
Section: Discussionmentioning
confidence: 99%
“…The lower aggregation energy in 1ZN À ÁH 2 O relative to other anionic forms is the result of presence of intramolecular H-bond present in the anion that decreases its ability to act as H-bond acceptor. The aggregation energy in the 1ZN À ÁH 2 O, 2EO4 À ÁH 2 O, 1EO À ÁH 2 O with single hydrogen bond interaction is 15 14.74 kcal/mol in TFHA. Though 2EO4 À ÁH 2 O adduct has highest stabilization arising out of H-bond interactions but this anion is not detected experimentally as the anion adduct stability is still lower than other anion adducts.…”
Section: Intermolecular H-bonding With Water In Anions Of Fha/tfhamentioning
confidence: 97%
“…Hydroxamate anions are regarded as a-effect nucleophiles whose reactivity is higher than predicted by relationship between nucleophilicity and basicity [13,14]. Explaining the role of HA's as matrix metalloprotease inhibitors, Yazal and Pang suggested that anionic forms of AHA have higher affinity for zinc relative to the HA molecules, thus probable binding involves anions [15].…”
Section: Introductionmentioning
confidence: 99%
“…For nucleophilic substitution reactions, it was shown that the solvent plays an important role in controlling the dynamics of a chemical reaction . The aminolysis of nitrophenyl acetates and dithiocarbonyl derivatives has shown interesting mechanistic changes by varying the solvent medium.…”
Section: Introductionmentioning
confidence: 99%